Cdc37 is a molecular chaperone with specific functions in signal transduction. - Kimura; Rutherford, S.L.; Miyata, Y.; Yahara, I.; Freeman, B.C.; Yue, L.; Morimoto, R.I.; Lindquist, S. (Genes & Development, 1997)
Cdc37 is required for cyclin-dependent kinase activation and is genetically linked with the activity of several other kinases, including oncogenic v-Src, casein kinase II, MPS-1 kinase, and sevenless. Strikingly, many pathways involving Cdc37 also involve the protein chaperone Hsp90. The identification of Cdc37 as the 50-kD protein in several Hsp90-kinase complexes, together with other data, led to the recent suggestion that Cdc37 is a kinase-targeting "subunit" of Hsp90. We directly examined the effect of Cdc37 on Hsp90 functions. Rather than simply acting as an accessory factor for Hsp90, Cdc37 is itself a protein chaperone with properties remarkably similar to those of Hsp90. In vitro, Cdc37 maintains denatured beta-galactosidase in an activation-competent state without reactivating it and stabilizes mature, but unstable, casein kinase II. In vivo, Cdc37 overexpression can compensate for decreased Hsp90 function, but the proteins are not interchangeable. Cdc37 can compensate for Hsp90 in maintaining the activity of v-Src kinase but does not maintain the activity of the glucocorticoid receptor. Thus, the very similar chaperone activities of the two proteins, uncovered through in vitro analysis, diverge in vivo in specific signal transduction pathways.